2015
DOI: 10.18632/oncotarget.6596
|View full text |Cite
|
Sign up to set email alerts
|

Liver irradiation causes distal bystander effects in the rat brain and affects animal behaviour

Abstract: Radiation therapy can not only produce effects on targeted organs, but can also influence shielded bystander organs, such as the brain in targeted liver irradiation. The brain is sensitive to radiation exposure, and irradiation causes significant neuro-cognitive deficits, including deficits in attention, concentration, memory, and executive and visuospatial functions. The mechanisms of their occurrence are not understood, although they may be related to the bystander effects.We analyzed the induction, mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 46 publications
0
29
0
Order By: Relevance
“…The BE has been observed in several species, suggesting it provides a beneficial effect that has been conserved through evolution (72)(73)(74). One consequence of BE is an adaptive response which renders bystander cells more resistant to future stressors (52).…”
Section: Cisplatin Evs Can Cause Bystander Effect and An Adaptive Resmentioning
confidence: 99%
“…The BE has been observed in several species, suggesting it provides a beneficial effect that has been conserved through evolution (72)(73)(74). One consequence of BE is an adaptive response which renders bystander cells more resistant to future stressors (52).…”
Section: Cisplatin Evs Can Cause Bystander Effect and An Adaptive Resmentioning
confidence: 99%
“…It is sensitive to a wide array of stimuli, including hormones, drugs, toxic chemicals, stress, and social experiences (Kolb et al, 2012 ). In our previous study, we showed that direct and bystander irradiation led to altered dendritic morphology and aberrant gene expression in the PFC tissues of exposed female rats (Kovalchuk et al, 2016 ). Here, for the first time, we show that very low, clinically, and occupationally relevant doses of radiation affect gene expression in the PFC in a sex-specific manner.…”
Section: Discussionmentioning
confidence: 95%
“…Mancuso et al ( 2008 , 2011 ) reported the presence of bystander effects in the cerebellums of mutant mouse strains following irradiation of the animals' bodies. Recently, we showed that directly irradiating a rat liver while shielding the rest of the animal caused distal systemic effects—molecular and neuroanatomical changes in brain and affected animal behavior (Kovalchuk et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our recent study published in the Oncotarget (2016) was the first to conduct a large-scale analysis of the molecular, neuroanatomical, and behavioral consequences of direct and bystander low-dose irradiation on the rodent brain. 41 The key findings were that: (i) direct head exposure to radiation doses as low as 24.5 cGy induced persistent, albeit small, increases in DNA damage, as measured by levels of gH2AX and effects on gene expression in the PFCs of exposed animals; (ii) bystander effects exist in the brain following liver irradiation and manifest as small increases in DNA damage, as measured by levels of gH2AX and alterations to gene and protein expressions; (iii) both head and liver irradiation reduce dendritic space (and, thus, synapse numbers) in measures of spine density, dendritic complexity, and dendritic length; (iv) the neuroanatomical effects are brain region-specific and are more pronounced in females; and (v) both head and liver irradiation alter behavior. 41 These intriguing bystander effects may be caused by certain blood-derived factors or by very small, scattered irradiation doses received by the brain.…”
Section: Direct Bystander and Scatter Low-dose Radiation Effects Onmentioning
confidence: 99%